Applying Use Case 2.0 Approach to The Development of IoT-Based Rainfall Monitoring System - Mohammad Fajar; Ferian Bagus Chandra; Hamdan Arfandy (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
The use of Internet of Things (IoT) technology for monitoring and controlling environmental conditions or objects is quite popular. However, most of the development of the IoT systems including rainfall monitoring systems, mainly focuses on the implementation perspective, rather than discussing the development approaches or design techniques. The use of suitable development approaches will increase maintainability aspect of the IoT system in the future. Therefore, the aim of this study is to implement and evaluate the use case 2.0 approach in modeling and designing an IoT-based monitoring rainfall system. Data collection was performed through evaluation using object-oriented metrics to measure encapsulation, polymorphism, and reusability properties of the designed system. In modeling the IoT system, collected requirements specifications are organized into user stories. The user stories are then mapped into UML use case diagrams. Each of the use case should be sliced into thinner pieces, taking into account of the basic and alternative flows of the user stories. Moreover, the use case slices are designed, implemented, and evaluated independently. The results of modeling and designing a rainfall monitoring system using the use-case 2.0 are then implemented on the NodeMCU platform and Android-based application. Evaluation results show that the implementation of use-case Reading, Viewing and Searching for Rainfall Data can be run successfully on the target platform. The measurement uses object-oriented metrics on the designed IoT system indicating that the use case slices have an impact on the ease of system modification level.